Máquina térmica quântica operando entre reservatórios de defasagem - Bernardo, Amanda Moreira (2024)
In this master’s dissertation, we propose a model for a quantum thermal machine operating an Otto cycle between local dephasing reservoirs. The working substance consists of a quantum system with two interacting sites. The dynamics of the working substance coupled to a dephasing thermal reservoir were deduced from a microscopic model, resulting in a Markovian master equation. Through coherent coupling between the two sites, we demonstrate that a local dephasing reservoir generates dissipative effects, in addition to the loss of quantum coherence. Consequently, it was possible to implement the isochoric processes that form the Otto cycle. We show that the thermalization time associated with these processes can be adjusted by varying the parameters of the two-site system. In cases where no thermalization occurs, the Otto cycle does not operate ideally, leading to a reduction in the efficiency of the thermal machine. However, we demonstrate that in such cases, ideal efficiency can be achieved as we increase the number of cycles executed by the thermal machine.